Interplay of the Organic Cation Transporters OCT1 and OCT2 with the Apically Localized Export Protein MATE1 for the Polarized Transport of Trospium - Deutsch, Birgit; Neumeister, Claudia; Schwantes, Ulrich; Fromm, Martin; König, Jörg (Molecular Pharmaceutics, 2019)
The anticholinergic drug trospium is secreted into urine and, to a smaller extent, into bile. Chemically, it is an organic cation, and it is a substrate of the uptake transporters OCT1 and OCT2 as well as for the export proteins MATE1 and MATE2-K as determined in uptake studies using HEK293 cells. So far, neither MATE-mediated export nor the interplay of OCT-mediated uptake and MATE-mediated export have been investigated. Therefore, we used polarized monolayers of single and double-transfected MDCKII cells (MDCK-OCT1, MDCK-OCT2, MDCK-MATE1, MDCK-OCTI-MATE1, and MDCK-OCT2-MATE1) and the respective control cells (MDCK-Co) for transcellular transport assays. We demonstrate that the trans cellular, basal-to-apical transport of trospium is significantly higher in all cell lines compared to control cells over nearly the complete concentration range tested. The transcellular transport mediated by double-transfected MDCK-OCTI-MATE1 and MDCK-OCT2-MATE1 exceeded that in the single-transfected cells (MDCK-OCTI-MATE1 vs MDCK-OCT1: 2.2-fold; MDCK-OCT1-MATE1 vs MDCK-MATE1: 1.7-fold; MDCK-OCT2-MATE1 vs MDCK-OCT2: 6.1-fold; MDCK-OCT2-MATE1 vs MDCK-MATE1: 1.8-fold at a trospium concentration of 1.0 mu M; p < 0.001 each). Thus, we show that MATE1 does not only mediate the uptake of trospium into HEK293 cells but also the efflux of trospium out of polarized MDCKII-cells. Furthermore, our results indicate that OCT1 or OCT2 as uptake transporters and MATE1 as an export protein contribute to the transcellular transport of trospium at concentrations normally reached during trospium therapy. These data suggest that both, OCT-mediated uptake as well as MATE1-mediated efflux may contribute to trospium renal and biliary elimination.
CRIS-Team WoS Importer:2019-02-21